Child Exploitation within the Illicit Narcotics Trade, as Described by Doen Pleger - Ahmad, Kamri (PRAWO i WIĘŹ, 2024)
In addition to the right to growth and development, every child is entitled to protection against violence and discrimination. Three rights should be bestowed upon children. In this context, the right to survival entails attaining self-sufficiency from childhood to adulthood. The entitlement to mature and progress. Individuals have the right to protection against violence and discrimination, which entails being free from unkind or unjust treatment and being subjected to appropriate treatment. The objective of this research is to assess the impact on the daily lives of children in Sidenreng Rappang regency who are exploited as delivery personnel for the illegal trade of narcotics, According to the results of the study conducted in October 2021 – January 2022. The interview questions pertaining to drug usage in this study were guided by the observational approach. Because they do not deserve it, children should not be expected to bear the same level of responsibility as adults in criminal and civil matters. In contrast, children are the nation’s most valuable resource and its future. Rehabilitation of drug users under the jurisdiction of the law narcotics should be reevaluated, as it not only imposes a significant financial burden on the state but is also frequently misconstrued in the policy of law enforcement.